Pengembangan Media ICT Berbasis Proyektor Interaktif Bagi Guru dan Siswa Raudhathul Athfal (RA) - Dindin Sobiruddin; Gelar Dwirahayu; Dedek Kustiawati (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2019)
Today's technology is increasingly dominating all aspects of life, including the use of technology in education, one of which is education at RA level. This research is integrated with community service activities which aim to train RA teachers to 1) utilize interactive projector-based ICT learning media in learning, 2) develop interactive projector-based ICT media for early childhood, 3) provide an overview of RA student activities in learning using interactive projector-based ICT media. Method The R&D method is used in developing interactive projector-based ICT applications and media to improve RA students' learning activities in the classroom. Interactive projector based ICT media trials were conducted in two RAs, namely RA Al-Hidayah students and RA Al-Husaeni students. Pandeglang district, Banten Province. The results showed that 1) arranged interactive learning applications for early childhood using interactive projector-based ICT media, 2) The thematic learning process in RA using interactive projector-based ICT media was very enjoyable, this was shown by the enthusiasm of students in participating in lessons and there is also an increase in the learning activities of RA students in Pandeglang Regency. 3) The teacher gives a positive response to the use of interactive projectors in thematic learning in class RA